Emergence of Colistin-Resistant Acinetobacter junii in China - Zhiren Wang; Xuanyang Fan; Shuyi Wang; Shuguang Li; Yue Gao; Hui Wang; Henan Li (MDPI AG, 2022)
The increasing number of multidrug-resistant Gram-negative bacteria presents a serious threat to global health. However, colistin-resistant Acinetobacter junii has rarely been reported. We identified a colistin-resistant A. junii clinical isolate, AJ6079, in blood. The colony of AJ6079 presented a dry phenotype, and it was difficult to form a bacterial suspension, whilst transmission electron microscopy revealed that AJ6079 possessed a thick outer membrane. The phenotypic and genomic comparisons were conducted with one colistin-susceptible A. junii, which had the same antibiotic susceptibility profile except for colistin, and had the same KL25 capsule biosynthesis locus. The AJ6079 exhibited a slower growth rate, indicating that colistin-resistant A. junii possesses a higher fitness cost. The genome of AJ6079 had a G+C content of 38.7% and contained one 3,362,966 bp circular chromosome with no plasmid or mobile colistin resistance (mcr) gene. Comparative genomic analysis revealed that the AJ6079 contained several previously unreported point mutations in colistin-resistance-related genes involving amino acid substitutions in PmrB (N5K, G147C), LpxA (I107F, H131Y), and LpxD (F20I, K263R), which might be correlated with colistin resistance in A. junii. Further research is needed for verification as the genetic background was not exactly the same between the two isolates.